Same-Sex Marriage and Other Moral Taboos: Cultural Acceptances, Change in American Public Opinion and the Evidence from the Opinion Polls - Marco Morini (European Journal of American Studies)
This article analyzes the evolution of gay and lesbian rights and same-sex marriage in American public opinion. It describes how Obergefell v. Hodges, state-level decisions and the public opinion trends can be considered as the outcome of a grassroots coordinated campaign which began more than a decade ago and was able to conquer the majority of Americans. It also focuses on the American public opinion trends related to moral issues, examining if it is true that U.S. citizens are moving leftward. The research shows that the shift toward more liberal attitudes on a number of social values and issues has occurred across the age spectrum, not just among young people, and that when Americans are asked about moral values they are thinking of things other than just the norms surrounding sexual behavior and reproduction issues. Thus, when Americans are largely saying that the overall moral tone of their culture is in bad shape and getting worse, they are only marginally thinking of former taboos such as gay and lesbian marriage and sexual behaviors in general.